Maps for time travelers how archaeologists use technology to bring us closer to the past - McCoy, Mark D., 1975- (University of California Press, 2020)
"Popular culture is rife with movies, books, and television shows that address our collective curiosity about what the world was like long ago. From historical dramas to science fiction tales of time travel, audiences love stories that reimagine the world before our time. But what if there were a field that, through the advancements in technology, can bring us closer to the past than ever before? Written by a preeminent expert in geospatial archaeology, Maps for Time Travelers is a guide to how technology is revolutionizing the way archaeologists study and reconstruct humanity's distant past. From satellite imagine to 3D modeling, today archaeologists are answering questions about human history that could only previously be imagined. As archaeologists create a better and more complete picture of the past, they sometimes find that truth is stranger than fiction"--